Parenting style and child weight-related outcomes : measurement, processes of influence, and the psychological context. - Taylor, Amanda May (My University, 2011)
Parents have been identified as key influencers of the child weight-related environment (Kitzmann, Dalton Iii, & Buscemi, 2008), but the understanding of this relationship remains unclear. In addition, the relationship between parenting, child weight and psychosocial outcomes remains relatively unstudied. This thesis addresses gaps in the literature by clarifying the influence of parenting on child weight and weight-related outcomes, through investigating the measurement of parenting, along with processes by which parenting style may show associations with child weight related outcomes. The first study involved an analysis of the longitudinal relationship between parenting style (at child age 4-5 years) and child Body Mass Index (BMI; at age 6-7 years). The study attempted to clarify the conclusions of a previously published study, which were based upon a particular scale argued to be inappropriate for measuring parenting style. This investigation found that fathers’, and not mothers’, parenting influenced child weight, with paternal ‘warmth’ predicting increased child weight. This was a surprising finding, but was thought to relate to paternal permissiveness. Three follow-up studies were conducted, utilizing a survey completed with children between the ages of 7 and 11 (n =233), their mothers (n=178) and fathers (n=85). The first investigation analysed two different measures of dimensions thought to comprise parenting style. The findings indicated that both mothers’ and fathers’ parenting was associated with child weight-related outcomes. Parental demandingness was not found to be associated with parental control, and parental responsiveness showed associations with parental warmth, but associations with child outcomes were not found to be equivalent. The second investigation focused on the relationship between child- and parent- reported parenting style, parental feeding and activity practices and child weight related outcomes. Both parenting styles and specific practices were found to be uniquely associated with child weight-related outcomes, but were not found to interact in their associations. Child-reported parenting style was associated with child diet and activity-related attitudes, whereas parent-reported parenting style was not associated with child weight-related indices. The final study investigated the relationship between parenting style and child weight-related psychological outcomes. Both child BMI and the parenting style dimension of responsiveness were associated with child psychological outcomes. Parenting was not found to moderate the association between child BMI and psychological outcomes. Both parenting styles and specific practices appear to be important for child weight-related behaviours. Importantly, a responsive parenting style was also associated with healthy psychological outcomes and should be encouraged in interventions attempting to influence weight: focusing solely on parenting practices may be insufficient. Researchers investigating parenting style should to ensure they examine the measures they intend to employ when considering the use of brief, proxy measures of complex constructs such as those that comprise parenting style. Finally, the child’s perspective appears to be important for understanding parental influence on child outcomes, and should be included wherever feasible.
Keywords: Health -- Obesity; Child Development; Families -- Parents and Parenting; Families and relationships; Childhood and child development; Health and wellbeing; Child Development; Health; Families; Parents and Parenting; Obesity; Families and relationships; Health and wellbeing; Childhood and child development